Seismic strengthening of R.C structures with exterior shear walls (Journal of Hama University, 2019)
Most of the existing buildings in Syria, may not meet the seismic design requirements. They may be subjected to a range of serious damage that may reach the point of collapse. To reduce seismic danger, existing buildings must be repaired and strengthened to increase their resistance for seismic acts, and thus to reduction physical and human damage.In this study, method of strengthening by adding external shear walls was carried out, 54 models with several variables (the rise of the phase, seismic zone, foundation soil) were analyzed .The analysis was done by the ETABS program according to the static method and the dynamic method (the response spectrum method) and then the results were discussed and  analyzed (base shear, period, total floor displacements, relative floor displacements, the occupancy rate of the shear wall)..The study showed the effectiveness of the strengthening by external shear walls, which increase the lateral stiffness so the building becomes able to resist the seismic  forces and thus reduce the damage caused by earthquakes and prevent any kind of  collapse.